Assessment of mobility, body balance and risk of fractures in the elderly - Ćwirlej-Sozańska, Agnieszka; Wilmowska-Pietruszyńska, Anna; Wiśniowska, Agnieszka; Guzik, Agnieszka; Drużbicki, Mariusz; Sozański, Bernard (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. In recent years, we have seen significant changes in the highly dynamic process of ageing amongst the population of Europe, leading to increasing life expectancy. Prolonging the life of the elderly, in which full independence and functional performance are maintained, is a challenge facing modern medicine. It is necessary to take actions to improve health and quality of life during old age. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Purpose. The aim of this research is to assess the differences in mobility level and static/dynamic balance, as well as the risk of bone fractures between people aged 50 and 65 years and the elderly aged between 66 and 80 years. An analysis of the suitability of selected clinical tests is conducted to assess the above mentioned parameters. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study included a group of 200 randomly selected people living in Rzeszów, a city in southeastern Poland, who were aged between 50 and 80 years. All the results of the research, which ultimately involved 138 people – 103 women and 35 men – have been analysed. To assess the mobility and static/dynamic balance, the following clinical tests were used: Timed Up and Go, Functional Reach, Tandem Stance, Tandem Walk and Tandem 180° Pivot. For the assessment of fracture risk, the Fracture Risk Assessment Tool (FRAX) calculator was used, while the data were collected on the basis of direct interviews. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. It was found that, with age, the frequency of dynamic balance, mobility disorders and the risk of bone fractures significantly increase. In a group of people aged 66 to 80 years, a decrease in the efficiency level of mobility and balance was observed in 30% of respondents on average, depending on the kind of functional test used (20-60%), in relation to people whose age did not exceed 65 years. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It is necessary to take preventive actions, especially amongst a group of people aged over 65 years, in order to improve functional efficiency and balance, thereby reducing the risk of fractures.